Análise econômica da eficiência do poder judiciário no combate da corrupção : aplicações de métodos de fronteira para os estados brasileiros (2003-2014) - Botelho, Martinho Martins (2016)
This study comprises an analysis of the efficiency of the judicial activities of the Brazilian judicial system against government corruption on State and Federal Courts through border non-parametric and parametric methods. We estimate rates and scores for a panel data of twelve years (2003-2014). We divided our studying into two parts: a theoretical and an empirical one. The theoretical part considers a literature review of Economics of Corruption. The other two parts consider a proposal to create an indicator of government corruption control by the Brazilian judicial system (ICC-PJ), that has a synthetic and composite character. It allows measuring the efficiency of the fight against government corruption by State and Federal courts in Brazil. For the efficiency analysis, we used DEA (BCC and CCR) and SFA, input oriented and output oriented. Actually, we confirmed that, despite recent corruption scandals in Brazil, and its relegation in the Corruption Perception Index of International Transparency (CPI-IT), the efficiency to combat corruptive acts has been increasing in the Brazilian courts. We have also found that the direct involvement of the National Council of Justice (CNJ) on Brazilian judicial system has caused a reducing effect on the inefficiencies in government corruptive control by the courts. Finally, DEA and SFA methods were also used in order to understand their limitations, advantages and disadvantages in measuring the efficiency of Brazilian courts